2015
DOI: 10.1128/mbio.01670-14
|View full text |Cite
|
Sign up to set email alerts
|

Gammaherpesvirus Small Noncoding RNAs Are Bifunctional Elements That Regulate Infection and Contribute to Virulence In Vivo

Abstract: Many viruses express noncoding RNAs (ncRNAs). The gammaherpesviruses (γHVs), including Epstein-Barr virus, Kaposi’s sarcoma-associated herpesvirus, and murine γHV68, each contain multiple ncRNA genes, including microRNAs (miRNAs). While these ncRNAs can regulate multiple host and viral processes in vitro, the genetic contribution of these RNAs to infection and pathogenesis remains largely unknown. To study the functional contribution of these RNAs to γHV infection, we have used γHV68, a small-animal model of γ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
86
2

Year Published

2015
2015
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(96 citation statements)
references
References 49 publications
8
86
2
Order By: Relevance
“…A practical consequence is that it might be inherently difficult to separate potential functions of the vtRNAs and miRNAs from each other. A first attempt in this direction was recently undertaken by Diebel et al 46,. suggesting an independent functional role of the vtRNAs in acute infection and pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…A practical consequence is that it might be inherently difficult to separate potential functions of the vtRNAs and miRNAs from each other. A first attempt in this direction was recently undertaken by Diebel et al 46,. suggesting an independent functional role of the vtRNAs in acute infection and pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study performed in pigs revealed that deletion of nine of the 11 miRNAs encoded in the large latency transcript of pseudorabies virus (PRV, suid herpesvirus 1) had little effect on latency establishment in the trigeminal ganglia (95). Recent studies have investigated the potential function of MuHV-4-encoded miRNAs in mice (96)(97)(98). Using MuHV-4 recombinant strains specifically deficient for the expression of viral miRNAs, the efficiency of B cell infection in vivo was only slightly affected.…”
Section: Survival and Proliferation Of Latently Infected Cells And Hementioning
confidence: 96%
“…These results suggest that ncRNAs, not only miRNAs, play major roles during infection in vivo and highlight the major importance of using genetically engineered recombinant viruses in animal models to address their roles in specific settings. Indeed, while the absence of MuHV-4 miRNAs did not significantly affect the colonization and latency in immunocompetent mice, impairment of MuHV-4 miRNA expression reduced the virulence of MuHV-4 infection in immunocompromised IFN-γ-deficient mice, suggesting a role in promoting gammaherpesvirus-associated disease (96,97). In addition, research conducted on malignant catarrhal fever (MCF), a T-cell lymphoproliferative cattle disease induced by OvHV-2 or alcelaphine herpesvirus 1 (AlHV-1) revealed the expression of a very high number of miRNAs after propagation of LCLs and in vivo (73,74).…”
Section: Survival and Proliferation Of Latently Infected Cells And Hementioning
confidence: 98%
“…Interestingly, a small cluster of EBV-encoded miRNAs has been shown to promote its transforming properties (Feederle et al, 2011). Although very little is known on the actual functions of c-HV-encoded miRNAs in vivo, two recent studies suggested that murid herpesvirus 4 (MuHV-4)-encoded miRNAs are not essential for viral replication or latency establishment in immunocompetent mice but potentiate the acute pathology induced by MuHV-4 infection in IFN-c-deficient mice (Diebel et al, 2015;Feldman et al, 2014).…”
Section: Introductionmentioning
confidence: 99%